Adaptive training of military cadets based on artificial intelligence algorithms - Kindzerska, A.H.; Karpushyna, M.H. (Київський інститут Національної гвардії України, 2025)
The implementation of adaptive learning systems based on AI algorithms in military education has immense potential for enhancing cadets’ training. However, the success of such transformation depends on a balanced combination of technological solutions, pedagogical expertise, data protection measures, and transparent governance policies. Careful design of pilot programs, continuous algorithm auditing, instructor training, and integration into the broader training architecture will ensure that adaptive technologies serve the ultimate goal: strengthening the competence and combat readiness of future military leaders while minimizing risks and maintaining human oversight of the learning process
Keywords: Тези; artificial intelligence (AI); Adaptive training of military cadets